2018
DOI: 10.1542/peds.2017-1026m
|View full text |Cite
|
Sign up to set email alerts
|

Parental Smoking Cessation: Impacting Children’s Tobacco Smoke Exposure in the Home

Abstract: This study provides evidence that tailored cessation offered to Ps/Cs in their children's schools during their children's enrollment in tobacco prevention may contribute to more robust success in P/C cessation and a reduction of tobacco smoke exposure in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…Electronic and hand searching identified 550 records, with 493 references remaining after the removal of duplicates. Based on title and abstract screening, 103 relevant articles were retrieved for full-text assessment, with the final inclusion of 16 primary controlled trials [ 5 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] (associated with 41 articles, Table S1 ). Twelve of these trials had previously been identified by Behbod and colleagues [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic and hand searching identified 550 records, with 493 references remaining after the removal of duplicates. Based on title and abstract screening, 103 relevant articles were retrieved for full-text assessment, with the final inclusion of 16 primary controlled trials [ 5 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] (associated with 41 articles, Table S1 ). Twelve of these trials had previously been identified by Behbod and colleagues [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Full trial characteristics are shown in Table S2 (including population, sample size, details of the intervention and control, outcome measures, and process indicators). Twelve trials [ 5 , 38 , 39 , 41 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 52 ] were randomised controlled trials (RCTs), three were cluster RCTs [ 40 , 50 , 51 ], and one was a non-randomised controlled trial [ 43 ]. Most trials were conducted in the USA [ 5 , 40 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 51 ], with the remaining trials in China [ 38 , 39 , 41 , 52 ], Germany [ 46 ], and Spain [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies have shown that SHS exposure was high among youth if their parents/guardians smoke 38,39 . With knowledge, the smoking parent/guardian might be more motivated to smoke outside the house 40 ; in addition, community intervention recruiting the adults should be intensified to promote smoke-free homes and increase the smoking cessation rate, which will ultimately reduce the SHS exposure at home 41 . Studies revealed that the implementation of a smoke-free home is possible with the consent of parents/guardians, especially in the patriarchal society of Malaysia 9 .…”
Section: Shs Exposurementioning
confidence: 99%
“…39 For example, it is well established that the combination of tobacco cessation counseling and first-line pharmacotherapy is more effective than either alone. 40 As well, caregiver smokers are more likely F I G U R E 3 Summary of solutions [Color figure can be viewed at wileyonlinelibrary.com] OATES ET AL.| 2337to quit when their children are simultaneously enrolled in a tobacco prevention program 41. To maximize success, interventions may aim to enroll all family members of the smoke-exposed child with CF in a tobacco cessation and prevention program.…”
mentioning
confidence: 99%